Gamers' interest in microtransaction activities at valve corporation - Desak Made Febri Purnama Sari; Niko Kurniawan; Ni Made Sumarningsih; Ida Nyoman Basmantra (Universitas Pendidikan Nasional, 2024)
The rapid growth of the online gaming industry has led to the rise of microtransactions, which have become a core component of the gaming experience. Valve Corporation, a prominent player in this industry, implemented a widely recognized microtransaction model through its platform. This study explored the factors influencing gamers in Bali to engage in microtransaction activities offered by Valve Corporation. Specifically, it investigated the effects of functional quality and price utility on purchase interest, with enjoyment serving as a mediating factor. The research targeted gamers in Bali who had previously engaged in microtransactions, employing an Accidental Sampling technique to collect data from 112 respondents. The analysis utilized Structural Equation Modeling - Partial Least Squares (SEM-PLS) to test the hypotheses. The findings revealed that functional quality and price utility both had significant positive effects on enjoyment and purchase interest. Furthermore, enjoyment not only directly influenced purchase interest but also mediated the effects of functional quality and price utility on purchase interest. These results highlight the critical role of enjoyment in shaping gamers’ decisions to participate in microtransactions, offering valuable insights for companies aiming to optimize their gaming platforms.